The value of invisibility: factors affecting social acceptance of renewable energy - Keeley, Alexander R.; Komatsubara, Kento; Managi, Shunsuke (Energy sources. Part B, Economics, planning and policy, 2022)
Notwithstanding the global turn to renewable energy, its development is constrained by a lack of social acceptance. Various studies have evaluated citizens' acceptance of and willingness to pay (WTP) for renewable energy and associated factors. We broadened the analytical framework of previous studies by incorporating spatial data on renewable and nonrenewable power plants, natural and produced capital, and renewable energy potential to determine key factors affecting social acceptance measured through WTP for renewable energy in Japan. We found that besides respondents' ages, sex, education levels, and household incomes, their proximity to existing power plants generating renewable and nonrenewable energy and natural capital endowments in their locations significantly affected their WTP for renewable energy. Our analysis further revealed that whereas visible solar PV plants located within 3 km of respondents' residences negatively affected their WTP, less visible plants at high elevations did not impact negatively on social acceptance.